Concentration and distribution of oil in the reservoir mineral Dolomite studied by neutron tomography (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Neutron Tomography – NT is a non-destructive technique, ideal for imaging hydrogen-rich substances even when wrapped up by thick rock layers. In the present study, the NT was employed for investigating the oil concentration and distribution in the mineral Dolomite, a natural oil reservoir. Two types of Dolomite samples, one of which dry, and the second one in oil-saturated were prepared. The applied oil was EMCAplus® 070 usually employed in permeability experiments to reproduce conditions of natural oil reservoirs. Three small fragments of the dry sample and three of the oil sample were inspected by NT and the comparison between the obtained results enabled, to distinguish several regions in which the oil is stored, to indicate that the oil is dispersed throughout the volume of the samples, and to quantify the storage concentration. The obtained data for oil concentration, for the three fragments, were compared to each other and to the one obtained by the conventional gravimetric technique, and they agreed within their uncertainties, demonstrating the viability of the NT technique to inspect, either in a qualitative as in a quantitative level, this oil reservoir mineral.